Protein synthesis elongation factor EF-1 alpha is essential for ubiquitin-dependent degradation of certain N alpha-acetylated proteins and may be substituted for by the bacterial elongation factor EF-Tu. - Gonen, H (1994)
Targeting of different cellular proteins for conjugation and subsequent degradation via the ubiquitin pathway involves diverse recognition signals and distinct enzymatic factors. A few proteins are recognized via their N-terminal amino acid residue and conjugated by a ubiquitin-protein ligase that recognizes this residue. Most substrates, including the N alpha-acetylated proteins that constitute the vast majority of cellular proteins, are targeted by different signals and are recognized by yet unknown ligases. We have previously shown that degradation of N-terminally blocked proteins requires a specific factor, designated FH, and that the factor acts along with the 26S protease complex to degrade ubiquitin-conjugated proteins. Here, we demonstrate that FH is the protein synthesis elongation factor EF-1 alpha. (a) Partial sequence analysis reveals 100% identity to EF-1 alpha. (b) Like EF-1 alpha, FH binds to immobilized GTP (or GDP) and can be purified in one step using the corresponding nucleotide for elution. (c) Guanine nucleotides that bind to EF-1 alpha protect the ubiquitin system-related activity of FH from heat inactivation, and nucleotides that do not bind do not exert this effect. (d) EF-Tu, the homologous bacterial elongation factor, can substitute for FH/EF-1 alpha in the proteolytic system. This last finding is of particular interest since the ubiquitin system has not been identified in prokaryotes. The activities of both EF-1 alpha and EF-Tu are strongly and specifically inhibited by ubiquitin-aldehyde, a specific inhibitor of ubiquitin isopeptidases. It appears, therefore, that EF-1 alpha may be involved in releasing ubiquitin from multiubiquitin chains, thus rendering the conjugates susceptible to the action of the 26S protease complex.